2017
DOI: 10.1097/bot.0000000000000878
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Delayed Diagnosis of Orthopaedic Injury in Pediatric Trauma Patients

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
1
5
0
2
Order By: Relevance
“…It is worth mentioning that these missed injuries did not result in mortality in our study. Similar findings in multiple other studies have shown that none of the delayed diagnoses contributed to the overall morbidity and mortality of the patients [5,10,11,13,19,27]. Out of the 476 patients who had a head injury or TBI, eight (1.7%) patients had a missed injury detected later during the hospital course.…”
Section: Prevalence Of Missed Injuries In Saudi Arabiasupporting
confidence: 86%
See 1 more Smart Citation
“…It is worth mentioning that these missed injuries did not result in mortality in our study. Similar findings in multiple other studies have shown that none of the delayed diagnoses contributed to the overall morbidity and mortality of the patients [5,10,11,13,19,27]. Out of the 476 patients who had a head injury or TBI, eight (1.7%) patients had a missed injury detected later during the hospital course.…”
Section: Prevalence Of Missed Injuries In Saudi Arabiasupporting
confidence: 86%
“…In Giannakopoulos et al, the missed injury population had a significantly higher median length of ICU stay of nine (3.7-16.2) versus five (2-11) days [11]. Podolnick JD et al had shown that the median ICU length of stay for pediatric patients with a missed injury was two days versus one day for patients without a missed injury [27].…”
Section: Predictors Of Missed Injuriesmentioning
confidence: 99%
“…23 Literatürde tanısal gecikme ile ilişkili görünen tekrarlayan faktörler, travmanın şiddetinin arttığı (ISS>15, injury severity score) yaralanma şiddeti skorunun yüksek olduğu durumlar ve hastanın mental durumunun kötüleşmesidir (Glaskow Koma Skalası <15). 24,25 Trafik ve motorlu araç kazalarında yaralanan hastalarda tanı atlama insidansının daha yüksek olduğu rapor edilmiştir. 26,27 hatalarıdır.…”
Section: Hasta Ile Ilgili Faktörlerunclassified
“…Glaskow Koma Skalası <15) 24,25. Trafik ve motorlu araç kazalarında yaralanan hastalarda tanı atlama insidansının daha yüksek olduğu rapor edilmiştir 26,27.…”
unclassified
“…[12][13][14]19,21,25,37 Medicaid/CHIP pediatric patients have been shown to wait 40 days longer for an appointment than those with private insurance, 8 which in orthopaedics has translated to more severe injury at time of surgery. 24,27,34 Meniscal tears account for one of the most common injuries among pediatric athletes. 50 The meniscus is integral to activity in children, playing a vital role in load bearing, load distribution, and overall knee stability, 14 with tears leading to significant long-term clinical effects.…”
mentioning
confidence: 99%